The outcome of short stay thyroidectomy in rural medical outreach settings in Northern Nigeria - Ale, Alexander F.; Isichei, Mercy W.; Misauno, Michael A. (International Journal of Research in Medical Sciences, 2020)
Background: The practice of short stay thyroidectomy is relatively new in developing nations like Nigeria. The primary reason for this is a lack of resources. Furthermore, the prevailing poverty prevents many patients from accessing tertiary health care, as such, ad hoc medical outreaches are usually conducted to bridge the gap. Thyroidectomies have not been routinely performed in these outreach settings due to safety concerns. The study seeks to analyse whether short stay thyroidectomy can be safely practiced under medical outreach settings with limited resources. Methods: The study is a prospective review of all patients that had short stay thyroidectomy at four rural medical outreach settings in Nigeria. Entire study spanned January 2019 to November 2019. Each outreach lasted one week, and patients were followed up for the duration of the outreach. All patients presenting at the outreach locations and diagnosed with goiters who have had no prior neck surgeries, are euthyroid, have no locally advanced malignancies or intrathoracic goiters, have adequate social support, possess a telephone, and have accommodation within the local government area where the outreach is carried out were included in the study. Exclusion criteria included patients who did not satisfy any of the above listed inclusion criteria. Thyroidectomy was done through a standard cervicotomy. Descriptive statistics were applied. Results: A total of 81 patients with non-toxic goiters had thyroid surgery. There were 76 (94%) females and five (6%) males. Average age was 46 years. Sixty-nine (85.2%) patients had no complication, while 12 (14.8%) patients had complications. Seventy-seven (95.1%) patients were discharged within 24 hours of surgery, while four (9.4%) patients were discharged within 48 hours. There was no mortality. Conclusions: The short-stay thyroidectomy model is feasible and safe in our environment, even in the presence of limited resources, and provides an alternative to the traditional 72 hour postoperative hospital stay.